Plastic regulates its co-pyrolysis process with biomass: Influencing factors, model calculations, and mechanisms - Wang, Zhiqiang; An, Shengwei; Zhao, Jian; Sun, Peng; Lyu, Honghong; Kong, Wenwen; Shen, Boxiong (Frontiers in Ecology and Evolution, 2022)
Co-pyrolysis of plastic and biomass can effectively improve the quality of bio-oil while solving the problem of plastic pollution. However, synergistic effect existed from co-pyrolysis on the kinetic characteristics is still not conclusive. In this work, the co-pyrolysis synergistic effects of three different hydrogen-to-carbon ratio (H/Ceff) of biomass-rice husk (RH), sugarcane bagasse (SUG), and poplar wood (PW) with hydrogen-rich polypropylene (PP) were studied using a thermogravimetric method. The total synergy degree (φ) and the difference between experimental and theoretical weight losses (∆W) were defined, and the activation energies of various experimental materials were calculated by the isoconversional method. The results showed that the addition of PP reduced the dependence of product species on biomass H/Ceff during co-pyrolysis. The synergistic effect of biomass and PP was related to biomass types, pyrolysis temperature, and mass ratio of biomass to PP. Compared with the theoretical value, the amount of biochar from SUG and PP decreased at all mass ratios and showed a positive synergistic effect. When the mass ratio of RH to PP was 1:3, the synergistic effect was the strongest, and the biochar was reduced by 36.00% from the theoretical amount. Simultaneously, three types of biomasses and PP were found to have an inhibitory effect on the pyrolysis of biomass at that mass ratio, which might be due to the melting of PP. Except for SUGPP3-1 and PWPP3-1, the positive synergistic effect (expressed as activation energy) of co-pyrolysis of all mixtures showed a decreasing trend with increasing conversion. The pyrolysis of rice husk followed Diffusion models (D2) and Nucleation model (A2) at low and high conversion rates, respectively, suggesting that a multi-step mechanism was observed in both the pyrolysis of a single sample and the co-pyrolysis of a mixture, according to Criado's schematic analysis. The study provides reference for selecting suitable biomass and PP co-pyrolysis in engineering applications.